Design of a systems analytics methodology to assess the impact of two urban transport interventions on social determinants of health indicators (2024)
The following doctoral dissertation describes the design of a systems analytics methodology to assess the possible impact of two urban transport interventions on social determinants of health. The methodology relies on systems theory techniques and data analytics techniques to describe, understand, and measure the system. The methodology was tested in two transport interventions: the implementation of temporary bike paths in Bogotá, and the implementation of a cable car as transit feeder in Bogotá.